2020
DOI: 10.1177/0022034520908593
|View full text |Cite
|
Sign up to set email alerts
|

Translation Approach for Dentine Regeneration Using GSK-3 Antagonists

Abstract: The canonical Wnt/β-catenin signaling pathway is crucial for reparative dentinogenesis following tooth damage, and the modulation of this pathway affects the rate and extent of reparative dentine formation in damaged mice molars by triggering the natural process of dentinogenesis. Pharmacological stimulation of Wnt/β-catenin signaling activity by small-molecule GSK-3 inhibitor drugs following pulp exposure in mouse molars results in reparative dentinogenesis. The creation of similar but larger lesions in rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 24 publications
0
33
0
3
Order By: Relevance
“…Following a dental intervention, the host biological response to treatment is to secrete tertiary dentine. In deep cavities, reparative dentine is formed and Neves et al 20 and Zaugg et al 28 showed that Wnt activation via GSK-3 antagonists enhances biologic reparative dentine repair in dental cavities. Reparative dentine formation, however, is a complex process that requires a mild inflammatory response within the tooth 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Following a dental intervention, the host biological response to treatment is to secrete tertiary dentine. In deep cavities, reparative dentine is formed and Neves et al 20 and Zaugg et al 28 showed that Wnt activation via GSK-3 antagonists enhances biologic reparative dentine repair in dental cavities. Reparative dentine formation, however, is a complex process that requires a mild inflammatory response within the tooth 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of an exogenous liposome‐reconstituted form of Wnt3A protein into mice molar pulps activated Wnt/β‐catenin signalling, promoted differentiation of odontoblast‐like cells and reduced apoptosis, culminating in a superior repair response 14 . Similarly, direct pulp capping of mice molars with glycogen synthase kinase 3 (GSK‐3) inhibitors, Wnt/β‐catenin signalling agonists, resulted in greater reparative dentine formation at pulp exposure sites when compared with plain collagen sponge or mineral trioxide aggregate 27‐29 . The reparative dentine was found to be close to native dentine compositions at defect sizes translatable to small human lesions 29 .…”
Section: Discussionmentioning
confidence: 99%
“…4 c) [ 44 ]. In a follow-up study, the authors took a closer look at the hard tissue formed in this model, now also in rats with even larger defects [ 46 ]. The formed tissue resembled dentin in its mineral composition, but no tubular structure was observed.…”
Section: Regeneration and Repair In The Dentin–pulp Complexmentioning
confidence: 99%
“…The formed tissue resembled dentin in its mineral composition, but no tubular structure was observed. Furthermore, it was shown that the pharmaceutical activity of the small-molecule inhibitor was spatially limited and without any systemic side effects [ 46 ].…”
Section: Regeneration and Repair In The Dentin–pulp Complexmentioning
confidence: 99%